Polyetheretherketone (PEEK): a contemporary modality in cranio maxillofacial reconstruction - Nada M. Fahmy (Advances in Medical, Pharmaceutical and Dental Research, 2022)
This descriptive review focuses on the evolution of polyetheretherketone [PEEK] for the reconstruction of cranio-maxillofacial defects. This treatment modality is now trending and growing throughout the different aspects of the oral and maxillofacial specialty to include customized patient specific implants for reconstructive surgeries, and a material that is used in dental implants. The PEEK implants are created using computer tomography [CT]to reconstruct the defect either in the midface or cranial defects and match with the opposite side, all implants were secured using screws. Cases were followed up for 12 months, and there were no postoperative problems. This came to an end that PEEK is considered as a safe and good implanted bone substitute for the fixation of complex defects of the cranio-maxillofacial.